Sinergitas Aktivitas Antibakteri dari Kelopak Bunga Rosella dan Kitosan Terhadap Staphylococcus aureus: Synergistic Antibacterial Activity of Roselle Calyx and Chitosan against Staphylococcus aureus - Haeriah, Haeriah; Djide, Natsir; Alam, Gemini; Sartini, Sartini (Universitas Tadulako, 2018)
Currently, the antibacterial research is increasingly promoted primarily from natural materials, due to the increasing number of pathogenic bacteria that have been resistant to existing antibiotics. One of the pathogenic bacteria that has been much resistant to antibiotics is Staphylococcus aureus. Rosella calyx (Hibiscus sabdariffa L.) and chitosan are known to have antibacterial activity. The aim of this study to find out the antibacterial synergy of the roselle calyx extract and chitosan against. S.aureus ATCC 33592. Rosella calyx was extracted by maceration using 80 % ethanol, while chitosan is obtained from deasetilation chitin of shrimp husk. Test antibacterial synergism using checkboard assay method by calculating the minimum inhibitory concentration (MIC) using microdilution assay. The results showed minimum inhibitory concentration (MIC) value of roselle calyx extract and chitosan were 1250 ppm and 50 ppm, respectively. MIC value of rosella calyx extract in the presence of chitosan was 625 ppm, while the value of MIC chitosan in the presence of rosella calyx extract was < 0.19 ppm. Fractional Inhibition Concentration Index (FICI) was < 0.5 which concluded that the combination of roselle calyx extract with chitosan has a synergistic antibacterial effect on S.aureus ATCC 33592.